Note—On Piecewise Reference Technologies - Färe, R.; Grosskopf, S.; Njinkeu, D. (Management Science, 1988)
In this paper we introduce a piecewise parametric production model that may be used as a reference technology for efficiency gauging. We show that other piecewise reference technologies used in efficiency measuring are obtained as special cases of our model.